(untitled) (GEOmedia, 2025)
Digital Twins are often presented as revolutionary tools for city management, infrastructure, and environmental stewardship. But what are they really? And, more importantly, are they truly applicable with effectiveness, or do they remain largely a narrative illusion built on unreliable data? In this article, we critically analyze the potential, limitations, and essential prerequisites to make these tools genuinely useful—starting from a frequently overlooked premise: without certified and accurate urban cartography, a digital twin holds no operational value.